2021
DOI: 10.3389/fnut.2021.723480
|View full text |Cite
|
Sign up to set email alerts
|

The Role of β-Carotene in Colonic Inflammation and Intestinal Barrier Integrity

Abstract: Background: Carotenoids are naturally occurring pigments accounting for the brilliant colors of fruits and vegetables. They may display antioxidant and anti-inflammatory properties in humans besides being precursors to vitamin A. There is a gap of knowledge in examining their role within colonic epithelial cells. We proposed to address this research gap by examining the effects of a major dietary carotenoid, β-carotene, in the in vitro epithelial cell model.Methods: We examined the function of β-carotene in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
2
17
0
1
Order By: Relevance
“…In Caco-2 cell layers challenged by endotoxin, pretreatment with Vitamin A significantly offset the ensuant TER reduction and reduced the decrease of occludin, claudin-1 and ZO-1 expression produced by endotoxin [ 336 ]. A similar finding was made in the HT-29 model with LPS and Vitamin A [ 337 ]. Similarly, Caco-2 cell layers made leaky (decreased TER) by exposure to Clostridium difficile toxin A were less leaky in the presence of Vitamin A [ 338 ].…”
Section: Can Elevated Micronutrient Levels (Supplementation) Improve ...supporting
confidence: 84%
“…In Caco-2 cell layers challenged by endotoxin, pretreatment with Vitamin A significantly offset the ensuant TER reduction and reduced the decrease of occludin, claudin-1 and ZO-1 expression produced by endotoxin [ 336 ]. A similar finding was made in the HT-29 model with LPS and Vitamin A [ 337 ]. Similarly, Caco-2 cell layers made leaky (decreased TER) by exposure to Clostridium difficile toxin A were less leaky in the presence of Vitamin A [ 338 ].…”
Section: Can Elevated Micronutrient Levels (Supplementation) Improve ...supporting
confidence: 84%
“…β-Carotene can also decrease the transcription of pro-inflammatory cytokine genes interleukin-1β (IL-1β), IL-6 and tumor necrosis factor alpha (TNF-α). 42 A reverse correlation between plasma β-carotene and C-reactive protein (CRP) has been reported earlier. 43 In LF it has been observed that CRP is over expressed in all clinical stages and the expression in chronic cases is almost double that of normal serum samples.…”
Section: Resultsmentioning
confidence: 88%
“…If this hypothesis is true, down regulating inflammation will improve hepatic steatosis caused by high sodium intake. β-carotene, a retinol precursor and antioxidant that is found in certain fruits and vegetables, has been found to have a strong anti-inflammatory effect [15][16][17]. Our second hypothesis, accordingly, is that high dietary β-carotene intake attenuates the effects of high sodium intake on NAFLD by down regulating inflammation.…”
Section: Introductionmentioning
confidence: 91%